The Influence Of Celebrity Endorsement, Brand Equity, And Features Services On Purchasing Decisions - Setia Pratama, Ade; Sudarmiatin, Sudarmiatin (International Journal of Science, Technology & Management, 2024)
The purpose of this research is to determine the influence of Celebrity Endorsement, Brand Equity, and Features Services on purchasing decisions (Study on TikTok Shop during January-March). Celebrity Endorsement, Brand Equity, and Features Services are the independent variables of this research. Purchase decision is the dependent variable. The Tiktok Shop application was used from 2021–2023 for this research. This research uses quantitative methods with primary data and data collection using questionnaires. This research analyzes data using multiple linear regression analysis.The partial test results show that (1) celebrity endorsements do not have a significant effect on purchasing decisions with a calculated value of tcount< ttable (0.045< 2.028) and a sig value.0.964 > 0.05 (2)brand equityhas a significant positive effect on purchasing decisions with tcount > ttable (2.206 > 2.028) and sig. 0.034 < 0.05 (3) feature services have a significant negative effect on purchasing decisions with tcount<ttable (0.927<2.028) and sig. 0.360 < 0.05. Meanwhile, the results of the simultaneous test show that Celebrity Endorsement, Brand Equity, and Features Services do not have a significant effect on purchasing decisions with valueFcount<Ftable (1.872 < 2.866) and sig value. (0.152>0.05).